Development of a scale to measure symptoms of anxiety and depression in the general UK population: the psychiatric symptom frequency scale. Issue 5 (October 1997) - Lindelow, M; Hardy, R; Rodgers, B
Abstract : OBJECTIVES: The psychiatric symptom frequency (PSF) scale was developed to assess symptoms of anxiety and depression (i.e. affective symptoms) experienced over the past year in the general population. This study aimed to examine the distribution of PSF scores, internal consistency, and factor structure and to investigate relationships between total scores for this scale and other indicators of poor mental health. PARTICIPANTS: The Medical Research Council national survey of health and development, a class stratified cohort study of men and women followed up from birth in 1946, with the most recent interview at age 43 when the PSF scale was administered. MAIN RESULTS: The PSF scale showed high internal consistency between the 18 items (Cronbach's alpha = 0.88). Ratings on items of the scale reflected one predominant factor, incorporating both depression and anxiety, and two additional factors of less statistical importance, one reflecting sleep problems and the other panic and situational anxiety. Total scores were calculated by adding 18 items of the scale, and high total scores were found to be strongly associated with reports of contact with a doctor or other health professional and use of prescribed medication for "nervous or emotional trouble or depression, " and with suicidal ideas. CONCLUSIONS: The PSF is a useful and valid scale for evaluating affective symptoms in the general population. It is appropriate for administration by lay interviewers with minimal training, is relatively brief, and generates few missing data. The total score is a flexible measure which can be used in continuous or binary form to suit the purposes of individual investigations, and provides discrimination at lower as well as upper levels of symptom severity.